Implications Of Land Ownership By Foreigners On The Investigation Process Of Criminal Acts By Foreigners - Afrihadi, Faisal; Harun, Rina Rohayu; Jiwantara, Firzhal Arzhi; Ufran, Ufran (IHSA Institute, 2025)
This study aims to analyze the practice of nominee agreements in land ownership by foreigners in Indonesia as a form of legal smuggling in a positive legal perspective. In the regulation of land law in Indonesia, based on the UUPA, land ownership with ownership rights is only by Indonesian citizens. The practice that occurs, foreigners through a name loan agreement to be able to control and own land in Indonesia with property rights. The normative legal research method with a statutory approach and a conceptual approach uses primary legal materials and secondary legal materials. Through literature studies (literature studies). The legal materials obtained were analyzed in a qualitative descriptive manner. The results of the study show that the nominee agreement is an agreement made between a person who according to the law cannot be the subject of a certain land right (property rights), in this case a foreigner with an Indonesian citizen, with the intention that the foreigner can control (own) the land owned de facto, but legally-formally (dejure) the land is owned on behalf of Indonesian citizens. The name loan agreement is clearly a form of legal smuggling to avoid regulations that stipulate that foreigners are not qualified as subjects of land title holders in Indonesia in accordance with the provisions in Article 9 paragraph (1) jo. Article 21 paragraph (1) of the UUPA clearly states that only Indonesian citizens can have a full relationship with earth, water and space, and clearly stipulates that only Indonesian citizens can have property rights